Kajian Literatur tentang Teknologi Berbasis Web sebagai Landasan dalam Pengembangan Program Inovasi “SI-Langkah Mandiri” (Sistem Informasi Lansia Gesit, Kuat, Aktif dan Harmoni dalam Manajemen Diri Hipertensi) - Ni Luh Putu Dian Yunita Sari; Etty Rekawati; Widyatuti Widyatuti (FORIKES, 2020)
Hypertension is the non-communicable disease that is highest identified in Indonesian older peolple. The purpose of this paper is to provide an overview of the application of technology, especially website-based applications in smartphones so that it can be a foundation in the development of the innovation program